The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1179/1743285513y.0000000036
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Al production methods

Abstract: The production of Al from its ores at present relies on the Bayer (alumina production) and the Hall-Heroult (Al production) process. The cost associated with alumina production and apparent disadvantages of the Hall-Heroult process have led to intensive research to find alternative routes for Al production. The direct carbothermal reduction process has been thoroughly investigated as an alternative technique. Another alternative includes the indirect carbothermal reduction route where alumina (or aluminous ore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…It was reported that aluminum nitride (AlN) can be formed by the reaction of Al 2 O 3 and carbon at 1400–1800°C in nitrogen or ammonia flow, and the oxidation of AlN is initiated at 850–900°C . In addition, the carbothermal reduction of Al 2 O 3 must be conducted above 2000°C to form Al 4 C 3 , and Al 4 C 3 is found to be stable to 1000°C in air . In our opinion, as Al 2 O 3 particles exist in the pores of the stabilized PAN fibers, it is unlikely they will be in contact with nitrogen to produce AlN during the carbonization.…”
Section: Resultsmentioning
confidence: 84%
“…It was reported that aluminum nitride (AlN) can be formed by the reaction of Al 2 O 3 and carbon at 1400–1800°C in nitrogen or ammonia flow, and the oxidation of AlN is initiated at 850–900°C . In addition, the carbothermal reduction of Al 2 O 3 must be conducted above 2000°C to form Al 4 C 3 , and Al 4 C 3 is found to be stable to 1000°C in air . In our opinion, as Al 2 O 3 particles exist in the pores of the stabilized PAN fibers, it is unlikely they will be in contact with nitrogen to produce AlN during the carbonization.…”
Section: Resultsmentioning
confidence: 84%
“…Other alternative ways to produce aluminum were reviewed. 141,[302][303][304] There were some proof of concept experiments using direct electrochemical reduction (DER) for Fe 305 and Al. 306 DER is a relatively new technique which was first developed and commercialized for Ti production; a recent review on this subject was published.…”
Section: Alternative Electrometallurgical Routesmentioning
confidence: 99%
“…Unfortunately, no correspondingly experimental study of thermal dissociation have been presented up to date. The theoretical decomposition voltage of AlN is 0.75 V at 973 K which is lower than that of Al 2 O 3(s) at the same temperature, but the major challenges is to find the appropriate electrolytes that can dissolve the very stable AlN [12].…”
mentioning
confidence: 95%